2021
DOI: 10.1017/s0022149x20001029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the helminth fauna in northern bobwhites (Colinus virginianus) occurring within South Texas

Abstract: Populations of northern bobwhites (Colinus virginianus; hereafter bobwhite) have been declining across their geographic range in North America, prompting consideration of the role parasites may play. We conducted this study to learn about the helminth fauna in South Texas, a region that supports a sustainable bobwhite population. Helminths were examined from 356 bobwhites collected during the 2014–2015 (n = 124) and 2015–2016 (n = 232) hunting seasons, when increasing trends in precipitation were observed in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…There was no variation between the sexes and ages of spurfowl in counts of A. suctoria. Similarly, previous authors reported an absence of differences in A. pennula infections across host age, sex and mass in northern bobwhites (Bruno et al 2019;Shea et al 2021). Both A. suctoria and A. pennula demonstrated the highest prevalence and were the numerically dominant species in their respective hosts.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…There was no variation between the sexes and ages of spurfowl in counts of A. suctoria. Similarly, previous authors reported an absence of differences in A. pennula infections across host age, sex and mass in northern bobwhites (Bruno et al 2019;Shea et al 2021). Both A. suctoria and A. pennula demonstrated the highest prevalence and were the numerically dominant species in their respective hosts.…”
Section: Discussionsupporting
confidence: 60%
“…This relatively fast accumulation of helminth species and numbers in the early phase of juvenile development might also explain why some studies obtained different results for the influence of host age on a given nematode species in the same host species. Olsen and Fedynich (2016) reported a higher prevalence and abundance of the subulurid Aulonocephalus pennula (Canavan, 1929) in adult than in juvenile northern bobwhites, while this did not differ in northern bobwhites from the same area collected during a later study (Shea et al 2021). However, fluctuating environmental conditions at the time of collection, influencing survival of free-living infective stages and abundance of arthropod intermediate hosts, might also have caused these differences (Crowe 2000;Calvete et al 2004;Olsen and Fedynich 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations